Compressive Strength of Concrete with Additions of Barley Bran Ash and Sugarcane Bagasse - Aranda Villanueva, Paul Absalón; Carrion Rabanal, Katia Nataly (LACCEI, 2024)
In the following research, materials are presented that will help improve the resistance to concrete f’c=210 kg/cm2, such as the use of sugarcane bagasse ash (CBCA) and barley ash (CAC) in percentages of 5%, 10% and 15%. Being an experimental investigation, standards and methods were used to carry out aggregate tests, these helped to make 126 cylindrical concrete specimens. The results obtained through the data collection instruments, which were processed in Excel program and allowed to obtain the results, which by incorporating 5% of CBCA, where it was determined that the addition of 5% of CBCA obtained greater compressive strength registering an increase of 36.66%, 28.72% and 29.67% at 7, 14 and 28 days of curing, additions of 10% and 15% of CBCA tend to raise resistance at 7 and 14 days by 19.30%, 24.61% and at 19.18%, 3.04% and at 28 days a decrease in resistance was recorded. On the other hand, additions of 5%, 10% and 15% with CAC on the other hand, generated a notable decrease in compressive strength, at all ages of 7, 14 and 28 days of curing.